ETNOGRAFI KOMUNIKASI KANURI LAOT MASYARAKAT NELAYAN KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Maifianti, Khori Suci; Raidayani, Raidayani (Jurnal AGRISEP, 2021)
This paper aims at analyzing the effect of Kanuri Laot in Samatiga, West Aceh, starting from the setting for preparation and the implementation of Kanuri Laot. The data were obtained through in-depth interviews with the implementing actors of Kanuri Laot accompanied by testing of interview data so that the data collected was tested. From the results of data testing, it was found that the preparatory setting was carried out indefinitely, it depended on the results of community deliberations. The implementation of the Kanuri Laot took place at Kuala Bubon beach with the implementation time being chosen on Sunday ofs every January.